From pandemic to endemic: Dynamics in the land border area Indonesia-Malaysia - Casiavera; Nikodemus Niko; Rizky Octa Putri Charin; Khairi Rahmi (The International Journal of Politics and Sociology Research, 2023)
The objective of this study is to analyze the impact of COVID-19 pandemic dynamics in the Entikong land border area between Indonesia and Malaysia, and how they may change as the virus becomes endemic. The Entikong region is highly susceptible to the spread of COVID-19 due to its significant cross-border traffic and trade. The exploratory descriptive method was employed, with primary data (interviews) and secondary data from desk review results related to the COVID-19 situation and its impact on communities in the border areas of the country. This study examines the impact of socio-economic situations on the spread of the virus. The findings suggest that the economic activity of the people in the Entikong region has been disrupted since the implementation of the border access closure due to the COVID-19 pandemic. This economic activity is regulated by the Border Trade Agreement (BTA), which has been in place since the 1970s, allowing economic activities in both regions of Indonesia and Malaysia. The pandemic has forced the border region to close all access to and from goods and people. However, our results also indicate that the region may be better equipped to manage the virus as it becomes endemic. The implications of our findings for policymakers and public health officials are discussed, emphasizing the need for ongoing monitoring and response efforts in the Entikong land border area. This study contributes to the existing literature on the impact of COVID-19 in border regions and provides insights that can guide policymakers in their efforts to mitigate the pandemic's impact on communities living in border regions.